Comparison of Vaginal Misoprostol and Prostaglandin E₂ for Labour Induction in Primigravidae: A Randomized Clinical Trial - Shazia Aftab, Mehmooda Memon, Humera Javed, Asim Iqbal Qureshi, Musserat Ashraf, Mehwish Zafar (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To compare the efficacy of vaginal misoprostol and prostaglandin E₂ (PGE₂) for induction of labour in primigravidae at term. Methods: This randomized clinical trial was conducted at the Department of Obstetrics and Gynaecology, Sohail Trust Hospital, Jinnah Medical and Dental College, Karachi, between September 1, 2022 and August 30, 2023. A total of 100 primigravidae at 37–42 weeks gestation requiring induction of labour were randomized into two equal groups. Group A received 100 µg misoprostol intravaginally every 4 hours (maximum 3 doses), and Group B received 3 mg PGE₂ pessary every 6 hours (maximum 2 doses). Primary outcomes included induction-to-delivery interval, oxytocin augmentation requirement, and mode of delivery. Secondary outcomes included fetal outcomes and adverse effects. Data was analyzed using SPSS version 20.0 by applying t-test to obtain the results. Ethical approval was obtained from the institutional review board of Jinnah Medical College hospital Karachi, and written informed consent was obtained from all participants and then questionnaire were being filled by doctor. Results: Mean induction-to-delivery interval was significantly shorter in the misoprostol group (10.96 ± 1.55 hours) than the PGE₂ group (13.06 ± 1.94 hours, p<0.001) [1]. Oxytocin augmentation was required in 44% of misoprostol patients versus 70% of PGE₂ patients (p=0.01). Vaginal delivery occurred in 94% of the misoprostol group and 74% of the PGE₂ group, while cesarean rates were 6% and 26%, respectively. No significant differences in Apgar scores or neonatal complications were observed. Conclusion: Vaginal misoprostol is a more effective, lower-cost option than PGE₂ for induction of labour in primigravidae at term, with a shorter induction-to-delivery interval and lower cesarean section rate, without compromising fetal outcomes. Keywords: Vaginal Misoprostol, Prostaglandin E₂, Labour Induction, Primigravidae, Randomized Clinical Trial